Analysis Hospital Competitor: A Market, Resources and Service Quality Based Framework Through Social Media - Prasetyorini, Anif; Drastyana, Serlly Frida; Puryanti, Puryanti; Angesti, Dyan (International Journal of Health and Information System, 2025)
The increasing number of hospitals requires them to segment the market. Hospitals can optimize marketing efforts, improve customer satisfaction, and achieve business goals more effectively. The purpose of the study to identify competitors and analyze hospital competitors based on market commonality, resource similarity and service quality. This type of research is quantitative descriptive research with a cross-sectional study approach. The population of this study is all hospitals with a maximum distance of 20 km from A Hospital, amounting to 8 hospitals. All secondary data analized by descriptive statistic. According to market commonality, “An” dan “K” hospital are hospitals that are direct competitor. Based on resurces similarity, “An”, “C”,  “K”  hospital are hospitals that are direct competitors. The weakness of service quality of direct competitors lies in the specialist doctor arrivals which do not comply with the established operational schedule and the quality of service which is less than satisfactory, starting from registration to purchasing medicine. So the way for hospitals to compete with direct competitors who have the same target market and resources must increase responsiveness, reliability and tangible aspects.